Efficient Green Quasi-Two-Dimensional Perovskite Light-Emitting Diodes Based on Mix-Interlayer - Wang, Zirong; Meng, Fanyuan; Feng, Qi; Shi, Shengxuan; Qiu, Langwen; Sun, Guanwei; Chen, Zhao; Zeng, Qingguang; Zhu, Weiguo; Su, Shi-Jian (Frontiers in Chemistry, 2022)
Recently, quasi-two-dimensional (Q-2D) perovskites have attracted much attention due to their unique photophysical properties. Phase compositions in Q-2D perovskites have obvious effect on the device performance. Here, efficient green perovskite light-emitting diodes (PeLEDs) were fabricated by employing o-fluorophenylethylammonium bromide (o-F-PEABr) and 2-aminoethanol hydrobromide (EOABr) as the mix-interlayer ligands. Phase compositions are rationally optimized through composition and interlayer engineering. Meanwhile, nonradiative recombination is greatly suppressed by the introduction of mix-interlayer ligands. Thus, green PeLEDs with a peak photoluminescence quantum yield (PLQY) of 81.4%, a narrow full width at half maximum (FWHM) of 19 nm, a maximum current efficiency (CE) of 27.7 cd/A, a maximum external quantum efficiency (EQE) of 10.4% were realized. The results are expected to offer a feasible method to realize high efficiency PeLEDs.